Perlindungan Hukum Kepada Pemilik Tanah Dalam Kasus Sengketa Perbatasan Tanah di Perkotaan - Geraldy Agavea Fernanda (Vidhisastya: Journal for Legalscholars, 2025)
Land boundary disputes in urban areas are complex issues that often cause ownership conflicts, legal uncertainty, and economic losses. This study aims to determine and analyze legal protection for land owners in border dispute cases and identify the causal factors and their impacts on ownership rights. This study uses a normative and empirical legal approach, with primary data obtained through interviews and field studies, as well as secondary data from laws and regulations, legal literature, and court decisions. The results of the study indicate that legal protection is divided into preventive (through PTSL, involvement of boundary witnesses, geospatial technology, public education) and repressive (through mediation, civil lawsuits, or criminal proceedings). However, its implementation still faces obstacles such as overlapping certificates, inaccurate measurements, and low legal literacy in the community. The main causes of disputes include weak land administration, minimal community participation, and abuse of authority by individuals. Border disputes have an impact on legal uncertainty, social conflict, and loss of land rights. Therefore, synergy is needed between the government and the community in strengthening the legal protection system and inclusive legal education.